Analisis Prinsip Kesopanan dalam Film Mononoke The Movie: Phantom In The Rain - Afifah, Hanan Dia; Zuliastutik, Hendri; Nugroho, Rahadiyan Duwi (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This research aims to describe the politeness maxims that might appear in the film Mononoke the Movie: Phantom in the Rain using the qualitative descriptive method. This film was chosen because it was released in 2024 and there has not been any research using this film as an object of research. The film also focuses on the characters’ trauma or tragedy instead of their relationship or connection with each other. This research uses Leech’s politeness principle to analyze the data obtained. The result of this analysis shows that there are 7 data that follow 4 politeness principles, which are: generosity maxim, probation maxim, modesty maxim, and agreement maxim. All of which are spread equally across 4 maxims.